2007
DOI: 10.1088/1464-4258/9/5/009
|View full text |Cite
|
Sign up to set email alerts
|

Self-started unidirectional operation of a fibre ring soliton laser without an isolator

Abstract: We demonstrate self-started mode-locking in an Erbium-doped fiber ring laser by using the nonlinear polarization rotation mode-locking technique but without an isolator in cavity.We show that due to the intrinsic effective nonlinearity discrimination of the mode-locked pulse propagating along different cavity directions, the soliton operation of the laser is always unidirectional, and its features have no difference to that of the unidirectional lasers with an isolator in cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In the lasers mode-locked solely by nonlinear polarisation evolution, the bidirectional operation could not be obtained only above the mode-locking threshold. As soon as the conditions for reaching mode-locking operation are fulfilled, one of the directions becomes dominant over another with around 10-dB extinction ratio, leading to quasi-unidirectional generation [ 181 , 182 ]. Therefore, the simplest ring cavity design uses material saturable absorbers ( Figure 8 b).…”
Section: Ultrafast Lasersmentioning
confidence: 99%
“…In the lasers mode-locked solely by nonlinear polarisation evolution, the bidirectional operation could not be obtained only above the mode-locking threshold. As soon as the conditions for reaching mode-locking operation are fulfilled, one of the directions becomes dominant over another with around 10-dB extinction ratio, leading to quasi-unidirectional generation [ 181 , 182 ]. Therefore, the simplest ring cavity design uses material saturable absorbers ( Figure 8 b).…”
Section: Ultrafast Lasersmentioning
confidence: 99%
“…For instance, in the lasers mode-locked by NPE the bidirectional generation could be achieved only bellow the mode-locking threshold, during continuous wave operation. As soon as the mode-locking was initiated, one of the directions dominates over another, giving, therefore, an isolator-free quasi-unidirectional generation with net extinction ratio around 10 dB [26,27]. Such behaviour refers to NPE mode-locking when the role of the nonlinearity-induced directional symmetry breaking is high.…”
Section: Introductionmentioning
confidence: 99%
“…Passively mode-locked fiber lasers have been extensively investigated as an excellent ultrafast pulse source because of their compactness, alignment-free operation and excellent pulse stability [1][2][3][4][5][6][7][8][9]. Dissipative solitons (DSs) were recently observed in all-normal-dispersion fiber lasers [1][2][3], which become a good alternative to solid-state lasers as they favor larger pulse energy compared to the solitons formed in the anomalous-dispersion regime and the dispersion-managed regime [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, an isolator was used to ensure the unidirectional operation. With a high power pump, Zhao et al reported self-started mode-locking and soliton operation in a bidirectional fiber ring laser mode locked by the NPR technique [7]. It was shown that due to the cavity nonlinearity-induced directional symmetry breaking the laser always operated unidirectional after mode-locking.…”
Section: Introductionmentioning
confidence: 99%